Two complementary methods for the identification and production of novel biomarkers of Plasmodium falciparum - García Ruiz, Oscar Andree (2016)
Ribosome profiling (RP) is a novel technique that exploits RNA sequencing and ribosome immobilization to quantify transcription and translation at different cell growth stages. Therefore, RP provides invaluable information for expression dynamics studies. Quantitative –omics studies are of crucial importance for identification of potential biomarkers of infection. An ideal parasite detection system should definitely establish the presence or absence of infection; determine the species involved; be detectable even in low concentrations; be proportional to parasite density; and determine the presence of antibiotic resistance.